Multiple sclerosis epidemiology in Finland: regional differences and high incidence - Pirttisalo AL; Soilu-Hänninen M; Sipilä JOT (Wiley, 2022)
OBJECTIVES:
Studies on the east-west gradient of multiple sclerosis (MS) are scarce. In Finland, epidemiological differences have been only partially elucidated, but the MS risk is high, and it has been claimed that the occurrence follows a longitudinal gradient. In this register-based study, we updated the MS epidemiology in southwest Finland (SwF) and compared it to the easternmost hospital district, North Karelia (NK), for which no previous data exist.
MATERIAL AND METHODS:
Patients with ICD-10 code G35 were identified from hospital district administrative data. Patient records were reviewed to include only cases with a definitive diagnosis. Incidence period covered 5 years (2012-2016) and the prevalence date was December 31, 2016. Results were standardized using the direct method.
RESULTS:
1184 persons had MS in SwF and 253 persons in NK at the end of 2016. The prevalence was 280/100,000 (95% Cl 264-296) in SwF and 168/100,000 (95% Cl 148-190) in NK (age-standardized for the European standard population 2013). During the incidence period, 211 new MS diagnoses were made in SwF and 49 in NK. The annual age-standardized (ESP 2013) incidence was 12.1/100,000 person-years (95% Cl 10.5-13.8) in SwF and 8.6/100,000 person-years (95% Cl 6.4-11.2) in NK in the age group 10-69 years.
CONCLUSIONS:
There are regional differences in MS epidemiology in Finland, possibly related to demographic, social and genetic circumstances but the retrospective nature and limited sample size of this study might introduce some uncertainty to the calculations. SwF is a region with a globally very high risk for MS. This article is protected by copyright. All rights reserved.